Adult Allogeneic Haematopoietic Stem Cell Transplantation: A Single Centre Experience in Malaysia - Gan, G.G.; Zakaria, Z.; Sangkar, J.V.; Haris, A.R.; Bee, P.C.; Chin, E.; Teh, A. (Malaysian Medical Association, 2008)
We analysed the outcome of 104 patients from a single institution who underwent allogeneic haematopoietic stem cell transplantation (AHSCT) from their HLA-identical siblings between 1993 and 2006. Sixty-nine percent of patients had peripheral blood stem cell (PBSC) as the stem cell source and the remaining had bone marrow (BM). The majority of patients are Chinese (60%) followed by Malays (24%) and Indians (14%). The median time to reach white cell counts of >1 x 10(9)/L and platelet counts of >30 x 10(9)/L was 13 and 15 days, respectively in patients who had PBSC transplantation compared with 16 and 25 days in patients who had BM transplantation, (p < 0.0001 and p < 0.001). Acute graft-versus-host disease (aGVHD) of grade II to IV was observed in 34% of patients and chronic graft-versus-host disease (cGVHD) in 38% of patients. Although not statistically significant, there was a higher incidence of overall aGVHD in Indian patients (73%) compared to Chinese and Malays (57% and 56% respectively). There was no significant difference in the incidence of aGVHD and cGVHD with the source of stem cells. Overall survival (OS) and disease free survival (DFS) was 50% and 60% at five years respectively. Multivariate analysis showed that patients transplanted in standard risk and those who had limited cGVHD had a significant better OS, (p = 0.05 and p = 0.05). Patients who had cGVHD and transplanted in standard risk had a better DFS, (p = 0.002 and p < 0.001). In summary, AHSCT in standard risk patients is associated with a better outcome than those transplanted in high risk and although not statistically significant, there is a higher incidence of aGVHD in Indian patients.